HIGH-REVOLUTION ROTARY FURNACE FOR FINE-GRAINED MATERIALS HEAT TREATMENT - Spisak, Jan; Nascak, Dusan; Hacevsky, Andrej (European Scientific Journal, ESJ, 2013)
Fine-grained and dust materials create a significant part of the thermally treated substances. The capabilities of materials processing are currently limited, thus making difficult its use. Rotary furnaces are contemporary the most important apparatuses for fine-grained materials processing. Apart from low efficiency, the process has also other limits that hinder their use for the fine-grained fractions heat treatment. The main problem of fine-grained materials processing lies in air tightness or low permeability of processed material layer. The concept of high-revolution rotary furnace was based on the mechanical fluidization of the material by which the homogeneous fluidized material layer through cross-section of the rotary furnace was obtained. Thereby homogeneous heating of individual grains was obtained. The research of mechanical fluidization was realized on the physical model of high-revolution rotary furnace. The pilot furnace design was based on the results of the experiment. The experiments focused on rheological, hydrodynamic and thermodynamic processes were conducted on this pilot high-revolution rotary furnace. The results of the experiments have confirmed correct functionality of the aggregate for the fine-grained materials heat treatment. The principal advantage of the furnace is the fluidization process which doesn’t depend on the flow and combustion processes